2016
DOI: 10.1371/journal.pgen.1005744
|View full text |Cite
|
Sign up to set email alerts
|

CFLAP1 and CFLAP2 Are Two bHLH Transcription Factors Participating in Synergistic Regulation of AtCFL1-Mediated Cuticle Development in Arabidopsis

Abstract: The cuticle is a hydrophobic lipid layer covering the epidermal cells of terrestrial plants. Although many genes involved in Arabidopsis cuticle development have been identified, the transcriptional regulation of these genes is largely unknown. Previously, we demonstrated that AtCFL1 negatively regulates cuticle development by interacting with the HD-ZIP IV transcription factor HDG1. Here, we report that two bHLH transcription factors, AtCFL1 associated protein 1 (CFLAP1) and CFLAP2, are also involved in AtCFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 83 publications
(100 reference statements)
2
13
0
Order By: Relevance
“…Consistent with previous studies ( Haslam et al , 2015 ; Lee and Suh, 2015 ; Li et al , 2016 ), the content of the unidentified components (which showed no significant differences among genotypes) was excluded from the total wax load.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Consistent with previous studies ( Haslam et al , 2015 ; Lee and Suh, 2015 ; Li et al , 2016 ), the content of the unidentified components (which showed no significant differences among genotypes) was excluded from the total wax load.…”
Section: Methodssupporting
confidence: 61%
“…Plant cuticular wax is a complex mixture of very-long-chain fatty acids (VLCFAs) and aldehydes, alcohols, alkanes, ketones, and esters, with predominant carbon chain-lengths ranging from C22 to C36 ( Samuels et al , 2008 ; Li et al , 2016 ), and it forms one of the major lipid components of the cuticle that covers the outer surface of aerial plant tissues. The biosynthesis of cuticular wax is processed through two distinct pathways, termed the alcohol-forming and the alkane-forming pathways, which yield 17~18% and 80% of the total amount of wax, respectively ( Bernard and Joubès, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies used Arabidopsis thaliana (L) Heynh as model for cutin biosynthesis (e.g., Nawrath et al, 2013 ; Go et al, 2014 ; Fabre et al, 2016 ; Li et al, 2016 ), but its cuticle composition is atypical and not representative for most plant species ( Franke et al, 2005 ; Pollard et al, 2008 ; Domínguez et al, 2011 ). Due to the increased availability of tomato ( Solanum lycopersicum L.) genomic resources, this fruit is also being used as model for analyzing the mechanisms of cuticle formation (e.g., Martin and Rose, 2014 ; Petit et al, 2014 ).…”
Section: Back To the Beginning: A Critical Examination Of The Prevailmentioning
confidence: 99%
“…CFLAP2 interacts with the C-terminal of CFL1 to regulate the downstream genes BODYGUARD ( BDG ) and FIDDLEHEAD ( FDH ), and negatively regulate cuticle development. When CFL1 or CFLAP2 is overexpressed, the expression of BDG and FDH are negatively regulated to decrease cuticle density, leading to defective cuticle development, which affects the differentiation of epidermal cells and changes the status of epidermal cells [43]. In the curly flag leaf 1 rice mutant, overexpression of CFL1 down-regulated the expression of BDG and FDH , which affected the development of leaf cuticle and led to the curly flag leaf phenotype [44].…”
Section: Resultsmentioning
confidence: 99%